2016
DOI: 10.1049/iet-rsn.2015.0170
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Pareto plus noise distribution parameters using non‐integer order moments and [zlog(z)] approaches

Abstract: Pareto plus noise clutter distribution has been introduced recently as a good candidate model for X-band high resolution maritime clutter returns. In this study, the authors derive a non-integer order moments estimator (NIOME) and [zlog(z)] based estimator to find the parameters of this distribution in the case of non-coherent integration of N-pulses. For this, the authors first develop an asymptotic formula of moments with non-integer order which is expressed in terms of the gamma and the generalised hypergeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
0
29
0
2
Order By: Relevance
“…Si bien algunos artículos han comenzado a aplicar la textura inversa gaussiana en diversos desarrollos (Chen et al, 2014;Gao, Zhan y Wan, 2014;Mezache et al, 2016;Yi, Yan y Han, 2014), la distribución no ha adquirido aún un alto grado de aceptación en la comunidad de modelación de clutter de radar. Este hecho se justifica, en parte, por el corto tiempo que ha transcurrido desde su aplicación inicial.…”
Section: Distribución Inversa Gaussianaunclassified
“…Si bien algunos artículos han comenzado a aplicar la textura inversa gaussiana en diversos desarrollos (Chen et al, 2014;Gao, Zhan y Wan, 2014;Mezache et al, 2016;Yi, Yan y Han, 2014), la distribución no ha adquirido aún un alto grado de aceptación en la comunidad de modelación de clutter de radar. Este hecho se justifica, en parte, por el corto tiempo que ha transcurrido desde su aplicación inicial.…”
Section: Distribución Inversa Gaussianaunclassified
“…In the reminder of Sec. 3, performance comparison between employment of RBF network as non-parametric model and traditional [zlog(z)] estimator [27], [28] in detection process is presented. Finally, concluding remarks and outline of future work is given in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, it has been suggested that this distribution provides better fits that the ones exhibited by the most popular alternatives (Farshchian & Posner, 2010). As a result, numerous recent investigations have applied the Pareto distribution in radar related applications (Mezache, Chalabi, Soltani, & Sahed, 2016;Rosenberg & Bocquet, 2015;Wang & Xu, 2014;Graham Victor Weinberg, 2013). The CUJAE's Radar Research Team has a great interest in developing Pareto based solutions, because this new model has a simpler PDF (Probability Density Function) compared to its counterparts K and KK, which will simplify the design and implementation of radar detectors.…”
Section: Introductionmentioning
confidence: 99%